Identification of a Cyanine-dye labeled peptidic ligand for Y₁R and Y₄R, based upon the Neuropeptide Y C-terminal analogue, BVD-15 - Liu, Mengjie; Richardson, Rachel R.; Mountford, Simon J.; Zhang, Lei; Tempone, Matheus H.; Herzog, Herbert; Holliday, Nicholas D.; Thompson, Philip E. (American Chemical Society, 2016)
Traceable truncated Neuropeptide Y (NPY) analogues with Y₁ receptor (Y₁R) affinity and selectivity are highly desirable tools in studying receptor location, regulation, and biological functions. A range of fluorescently labeled analogues of a reported Y₁R/Y₄R preferring ligand BVD-15 have been prepared and evaluated using high content imaging techniques. One peptide, [Lys²(sCy5), Arg⁴]BVD-15, was characterized as an Y₁R antagonist with a pKD of 7.2 measured by saturation analysis using fluorescent imaging. The peptide showed 8-fold lower affinity for Y₄R (pKD = 6.2) and was a partial agonist at this receptor. The suitability of [Lys²(sCy5), Arg⁴]BVD-15 for Y₁R and Y₄R competition binding experiments was also demonstrated in intact cells. The nature of the label was shown to be critical with replacement of sCy5 by the more hydrophobic Cy5.5 resulting in a switch from Y₁R antagonist to Y₁R partial agonist.